Meditasi Mindfulness dengan Deep Focus Music terhadap Tekanan Darah dan Stres pada Penderita Hipertensi Lanjut Usia - Elina Situmorang; Neti Juniarti; Agus Riyanto; Nurharlinah Nurharlinah; Oop Ropei (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effectiveness of mindfulness meditation with deep focus music on blood pressure and stress in elderly hypertensive patients at the Sukabumi Nursing Home. This research is a quasi-experimental study with a non-equivalent control group with a pretest and posttest. The results showed that all sexes were female, with 17 people (100%) in the control and intervention groups aged 60-70. Eight people (47.1%) were in the intervention group and the control group, six people (35.3%) aged> 70 years, nine people (52.9%) in the intervention group, and 11 people (64.7%) in the control group, had no comorbidities in the intervention group 12 people (70.6%). The control group, 14 people (82, 4% 5), had comorbidities. In the intervention group, five people (29.4%). The control group, three people (17.6%), did not take hypertension herb medicine, and the intervention group and the control group, 17 people (100%). No physical exercise was done in the intervention group, and in the control group, 17 people (100%). In conclusion, mindfulness with deep-focus music effectively affects systolic blood pressure and stress levels. In contrast, on diastolic blood pressure, mindfulness meditation with deep focus music at the Sukabumi Nursing Home has no effect. Keywords: Deep Focus Music, Hypertension, Elderly, Mindfulness Meditation, Stress